Predictors of Sixth-Grade English Reading Performance in Adventist Schools in Mindanao, Philippines - Vasquez, Olivia Borci (JPAIR Multidisciplinary Research, 2009)
The main purpose of this study was to determine the significant child, home, and school reading-related predictors of the sixth-grade English-reading performance. Employing the step by step cluster random sampling, 10 schools located within the cities of Mindanao, Philippines, which is run and operated by the Seventh-day Adventist church, were selected. There were 335 sixth graders, which is 91% of the targeted sample of 369 from the total population of 630. These 335 respondents were composed of 157 girls and 178 boys with an average age equivalent to 11.9 years old. Most of them came from Cebuano homes, which is equivalent to 73.1%. This quantitative study employed the descriptive-correlational design. It was established in this study that personal characteristics, as well as the home and school environments are factors of English-reading performance of the sixth graders. It is important to note that positive attitude towards reading and exposure to the varied classroom reading events are significant considerations in the nurture of a school child towards academic success. The challenge of increasing the reading performance of school-age boys continues. Likewise, the education of mothers and mothers to be is vital.